EFFECT OF DIFFERENT PACKAGING TYPES TOWARD THE QUALITY OF GOLD FISH (Cyprinus carpio)BABY CHIPS DURING ROOM TEMPERATURE STORAGE - Rahman Hidayat; Suparmi Suparmi; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was aimed to determine theeffectof different packaging types towardthe qualityof goldfish baby chips during room temperature storage. The research method used was experimental method with Completely Randomized Design (CRD)consisting of 2 treatment levels of different packaging types i.e. HDPE plastic (K1), and Combination plastic (HDPE and aluminum foil) (K2). The quality parameters tested in this study were proximate test (moisture, fat, protein content) organoleptic test (appearance, aroma, texture, taste) and mold. The result showed that the goldfish baby chips packed with combination plastic stored at room temperature was the best treatment, whereas the organoleptic value for appearance6.68, aroma 6.72, texture 5.28, and taste6.04. Meanwhile for proximate values that gold fish fish baby chips containing moisture, fat, protein content and mold were 24.71%, 10.78%, 32.19% and,2,4x102, respectively. Key words:Fish baby chips, gold fish, packaging types,temperature storage